Determinants of pulmonary vascular resistance reduction with upfront oral therapy in idiopathic pulmonary arterial hypertension: relevance in risk assessment. (25th November 2020) - Badagliacca, R; D'Alto, M; Ghio, S; Greco, A; Papa, S; Romeo, E; Casu, G; Corda, M; Paciocco, P; D'Agostino, C; Galgano, G; Stolfo, D; et al.
Abstract: Background: In pulmonary arterial hypertension (PAH) upfront oral therapy represents the standard of care for naive patients at low and intermediate risk. However little is known about associated changes in risk assessment and prediction of low risk status achievement. Purpose: To evaluate determinants of PVR reduction in patients treated with upfront oral therapy and to create a score to predict PVR reduction after upfront oral treatment and compared its additive value on top of the European and REVEAL scoring system in predicting treatment response. Methods: One-hundred-eighty-one consecutive naive PAH patients treated with upfront therapy at 11 italian centers were retrospectively evaluated. Evaluation included clinical, hemodynamic and simple echocardiographic parameters, together with European and REVEAL 2.0 risk scores. Results: At the time of diagnosis, the majority of the patients was idiopathic PAH (80.6%), female (66.3%), at intermediate risk, 71.8% and 55.2%, respectively, according to the European (average method) and the REVEAL 2.0 risk scores. Ambrisentan-Tadalafil was the most frequent combination used (62%). The median PVR reduction obtained after 180 days (IQR 79–394) was −40.4% (IQR −25.8; −45.3). Age ≥60 years, male-sex, baseline mPAP 48 mmHg associated with low CI (<2.5 l/min/m 2 ), and RV/LV ratio >1 associated with low TAPSE (<18 mm) emerged as independent predictors of poor PVR reduction, defined as the lower tertile of PVR changes (−25.8%). A treatment response score was created deriving weighted integers from the beta coefficient. At second evaluation 78 (43.1%) patients achieved or remained at European-derived low risk status, while 63 (34.8%) considering the REVEAL 2.0 score. Multivariate analysis for the prediction of treatment failure, defined as the absence of low-risk status at follow-up, demonstrated the incremental prognostic power of the models incorporating the treatment response score (≥3) on top of the European and REVEAL 2.0 scores, improving risk discrimination by 63.2% (IDI index 0.056) and 36.8% (IDI index 0.080), respectively. Conclusions: A significant proportion of PAH patients treated with upfront oral combination are not able to achieve a low-risk status. The treatment response score helps clinicians in predicting treatment failure at the time of diagnosis. Funding Acknowledgement: Type of funding source: None